2011
DOI: 10.1080/10473289.2011.639480
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions from 20 landfills across the United States using vertical radial plume mapping

Abstract: Landfill fugitive methane emissions were quantified as a function of climate type and cover type at 20 landfills using U.S. Environmental Protection Agency (EPA) Other Test Method (OTM)-10 vertical radial plume mapping (VRPM) with tunable diode lasers (TDLs). The VRPM data were initially collected as g CH 4 /sec emission rates and subsequently converted to g CH 4 /m 2 / day rates using two recently published approaches. The first was based upon field tracer releases of methane or acetylene and multiple linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 15 publications
2
57
0
6
Order By: Relevance
“…Vertical radial plume mapping. The vertical radial plume mapping (VRPM) method makes use of an optical remote sensing instrument (ORSI) to quantify the path integrated CH 4 concentrations in a perpendicular plane downwind of the source at five radial distances (Abichou et al, 2010(Abichou et al, , 2012Goldsmith et al, 2012;Hashmonay et al, 2001 Goldsmith et al (2012). The sources of uncertainties in the VRPM method were initially examined by Abichou et al (2010).…”
Section: Tracer Correlation Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…Vertical radial plume mapping. The vertical radial plume mapping (VRPM) method makes use of an optical remote sensing instrument (ORSI) to quantify the path integrated CH 4 concentrations in a perpendicular plane downwind of the source at five radial distances (Abichou et al, 2010(Abichou et al, , 2012Goldsmith et al, 2012;Hashmonay et al, 2001 Goldsmith et al (2012). The sources of uncertainties in the VRPM method were initially examined by Abichou et al (2010).…”
Section: Tracer Correlation Approachmentioning
confidence: 99%
“…However, significant variability was observed for the VRPM data. We note that Goldsmith et al (2012) reported the standard error and the number of measurements conducted downwind of the intermediate and final cover areas of IN-1. To be consistent with the reporting of the uncertainties for all measurement approaches, we calculated the standard deviation of the VRPM measurements.…”
Section: Area-specific Emissions: Spatial Variability and Uncertaintymentioning
confidence: 99%
See 3 more Smart Citations